2013
DOI: 10.1108/13287261311328877
|View full text |Cite
|
Sign up to set email alerts
|

Extending customer relationship management: from empowering firms to empowering customers

Abstract: PurposeThe focus of customer relationship management (CRM) literature has been predominantly on the firm perspective and on IT, not on customer or service orientation and value co‐creation. This paper seeks to explore and analyse contemporary CRM frameworks and suggests future research directions. To achieve this, a thorough literature review on CRM is conducted focusing on recent advances within CRM. This provides a good basis for critically analysing the current status of both CRM theory and practice.Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 72 publications
(53 reference statements)
1
18
0
Order By: Relevance
“…The empowerment of the customer has naturally generated new challenges for customer relationship management (CRM). As Saarijärvi et al (2013) concluded, 'CRM must adapt to a business environment where new forms of exchange are emerging and where traditional customer and firm roles quickly become out-dated and are recreated ' (p.152).…”
Section: Introductionmentioning
confidence: 99%
“…The empowerment of the customer has naturally generated new challenges for customer relationship management (CRM). As Saarijärvi et al (2013) concluded, 'CRM must adapt to a business environment where new forms of exchange are emerging and where traditional customer and firm roles quickly become out-dated and are recreated ' (p.152).…”
Section: Introductionmentioning
confidence: 99%
“…One criticism of CRM is that study and implementation are too dominated by the perspective of information technology and information systems. Even though it should also take into account service or customer orientation and value co-creation (Saarijarvi, Karjaluoto, & Hannu, 2013) (Steinhoff & Palmatier, 2016)).…”
Section: Introductionmentioning
confidence: 99%
“…General concepts and fragmented research were caused by domains operating at several levels of analysis: conceptual, empirical, and practical (Lainamngern, 2019). (Saarijarvi et al, 2013) argues that one of the bases of CRM is that customer data is used for the profit of the company, to be exact as main supply for company processes. Through CRM, events such as cross-selling, marketing communications are adjusted or segmented, the potential worth of customer data is processed into data and information for companies to be able to market more products and to manage better customer relationships (Saarijarvi et al, 2013) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Saarijärvi et al (2013) starting from the analysis of the literature published from 2003 to 2011on customer relationship management (CRM) frameworks a conceptual framework of the changing role of customer data in the CRM framework is provided.…”
Section: Introductionmentioning
confidence: 99%